Effect of Board’s Skills on Stakeholder Value - Chaabouni, Ines; Jarboui, Anis (Asian Journal of Empirical Research, 2016)
The aim of this paper is to discuss the effect of the board’s capital on the firm value by the intermediation of the board’s functions. We took a sample of 73 Tunisian public limited companies and we tested the direct impact of the board’s functions on the firm value and its mediator role on the relationship between board’s capital and firm’s value by using structural equations. Our results show that only the board’s cognitive function has an impact on shareholder and stakeholder value. In fact, the board’s disciplinary function loses its signification by integrating the skills and competencies of directors. Moreover, the board’s cognitive function plays a mediator role between the board’s capital and the firm’s value. Our study aims to stress the new role of the board of directors as a provider of skills and expertise that can ameliorate the value of the firm by assisting the manager in making adequate decisions.